EMI filter design for matrix converters in airspace applications - Degano, Marco (2012)
Advanced power electronics systems are increasingly being used for AC motor drives, due to their numerous advantages in terms of performance and flexibility; however, due to their switching behaviour, they introduce significant harmonic content. To reduce any interaction with other appliances suitable EMI filters need to be designed and implemented.